2022
DOI: 10.3389/fgene.2022.790690
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Key Genes and Functionally Enriched Pathways of Diverse Adipose Tissue Types in Cattle

Abstract: Background: Fat is a tissue that not just stores energy and plays a protective role; it is also a vital endocrine organ that generates and integrates signals to influence metabolism. Meanwhile, the excessive accumulation of lipids in adipose tissue can lead to metabolic disturbance and diseases. To date, the complicated molecular mechanisms of bovine adipose tissue are still unknown. This study aimed to identify key genes and functionally enriched pathways in various adipose tissue types.Results: The RNAseq da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Among these, circRNA 21:6969877|69753491 has been shown to be involved in lipid metabolism in a previous study, therefore it likely affects fat deposition. Gene significance (GS>0.8) ( 37 , 38 ) and module membership (MM>0.8) ( 37 39 ) values showed a high correlation between circRNA 21:6969877|69753491 and two traits (month and weight) of buffalo Figure 1F .…”
Section: Resultsmentioning
confidence: 99%
“…Among these, circRNA 21:6969877|69753491 has been shown to be involved in lipid metabolism in a previous study, therefore it likely affects fat deposition. Gene significance (GS>0.8) ( 37 , 38 ) and module membership (MM>0.8) ( 37 39 ) values showed a high correlation between circRNA 21:6969877|69753491 and two traits (month and weight) of buffalo Figure 1F .…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we found a strong positive correlation ( r > 0.9, p < 3.40 × 10 −14 ) between ARID4A and genes such as AHI1 , AKAP9 , ANKRD12 , CCDC18 , ENSSSCG00000037142 , IFT74 , KIAA2026 , NEXN , PPIG , ROCK1 , SMC4 , TWISTNB , BAZ1A , EIF5B , NSRP1 , and BBX . Among these genes, AHI1 , AKAP9 , ANKRD12 , CCDC18 , IFT74 , NEXN , etc., have been shown to play an important role in adipose deposition or obesity [ 48 , 49 , 50 , 51 , 52 , 53 ]. Moreover, AHI1 , AKAP9 , ANKRD12 , CCDC18 , IFT74 , KIAA2026 , NEXN , PPIG , ROCK1 , SMC4 , TWISTNB , EIF5B , and NSRP1 were also identified as potentially related to adipose deposition in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, ANKRD12 , ARID4A , IFT74 , KIAA2026 , and ROCK1 are located in multiple fat-related QTLs, and ANKRD12 , CCDC18 , NEXN , PPIG , and ROCK1 , are present in the intramuscular fat content QTL. Reports have already shown that ANKRD12, NEXN, IFT74, and ROCK1 play an important role in adipose deposition or obesity [ 50 , 52 , 53 , 56 ]. While CCDC18 is a new marker gene for fatty liver in chicken [ 51 ], its role in fat deposition has been rarely reported.…”
Section: Discussionmentioning
confidence: 99%
“…The gene co-expression network was constructed by using WGCNA software package in R ( Pan et al, 2022 ). First, a similarity matrix was constructed by calculating Pearson correlation coefficients.…”
Section: Methodsmentioning
confidence: 99%